Inside vanguard : leadership secrets from the company that continues to rewrite the rules of the investing business - Ellis, Charles D. (McGraw-Hill Education, 2023)
"This rare intimate look at Jack Bogle and his world-changing investment organization provides invaluable lessons for investors, for business leaders, and for historians of finance"--